The “Network Effect” in Management: Social Network Analysis (SNA) - Praszkier, Ryszard (Journal of Positive Management, 2025)
Purpose: This article delves into the nature of horizontality in management, delineating both its qualitative and quantitative features. It is the first attempt to determine the preconditions for achieving the network effects, i.e., the impact generated by the connectivity between network participants. Design/methodology/approach: The theoretical part is based on literature review. The research method is social network analysis (SNA), showing the properties of the entire network, as well as the features of all individual participants’ positions. SNA demonstrates sociograms and their diverse visualizations. Findings: The study demonstrated 683 connections between the 77 nodes, each of them on average establishing 8.87 connections with others. The density of the entire network is 11.7%, and the average path length is 1.95. 290 cooperation lines were identified, meaning that 290 peer-to-peer projects have been initiated. Each node has established, on average, 3.77 cooperative connections. Social implications: Horizontal social networks, through providing satisfaction and support (Hirsch 1979), are an important value-added for both business as well as social organizations. The SNA method provides tangible ways to determine key properties of productive networks. Limitations: The study is based on one social network.It would be valuable to include in future studies also other social network. Originality/value: This article addresses an original and underexplored topic — the operationalisation of the network effect in the management of social organisations. The proposal to identify structural thresholds as interpretive hypotheses constitutes a novel contribution to the literature. Keywords: Social networks, SNA, connectivity, cooperation, peer-to-peer communication, horizontality. Paper type: Research paper.